2016
DOI: 10.1371/journal.pone.0166106
|View full text |Cite
|
Sign up to set email alerts
|

Fast-to-Slow Transition of Skeletal Muscle Contractile Function and Corresponding Changes in Myosin Heavy and Light Chain Formation in the R6/2 Mouse Model of Huntington’s Disease

Abstract: Huntington´s disease (HD) is a hereditary neurodegenerative disease resulting from an expanded polyglutamine sequence (poly-Q) in the protein huntingtin (HTT). Various studies report atrophy and metabolic pathology of skeletal muscle in HD and suggest as part of the process a fast-to-slow fiber type transition that may be caused by the pathological changes in central motor control or/and by mutant HTT in the muscle tissue itself. To investigate muscle pathology in HD, we used R6/2 mice, a common animal model f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 66 publications
(93 reference statements)
1
16
0
Order By: Relevance
“…GLUT4 expression compared to fast fiber [52,53]. Similar changes are seen in cancer cachexia [54], aging-related sarcopenia [55], and Huntington's Disease [56]. The differences in the slow fiber area between the MHP (rat) and GDM (human) groups may be due to the relatively short pregnancy time and the higher number of fetuses in the rats and high weight gain in the humans.…”
Section: Plos Onementioning
confidence: 76%
“…GLUT4 expression compared to fast fiber [52,53]. Similar changes are seen in cancer cachexia [54], aging-related sarcopenia [55], and Huntington's Disease [56]. The differences in the slow fiber area between the MHP (rat) and GDM (human) groups may be due to the relatively short pregnancy time and the higher number of fetuses in the rats and high weight gain in the humans.…”
Section: Plos Onementioning
confidence: 76%
“…In support of primary muscle defects, motor symptoms were shown to precede the onset of neurological symptoms in a marathon runner with HD (Kosinski et al, 2007). Moreover, a number of studies have demonstrated pathological changes in HD muscle, including metabolic and mitochondrial defects (Lodi et al, 2000;Turner et al, 2007;Mielcarek et al, 2015), atrophy (Ribchester et al, 2004;She et al, 2011;Ehrnhoefer et al, 2014), reduced muscle strength (Busse et al, 2008;Hering et al, 2016), and a reduced expression of genes necessary for normal muscle differentiation (Luthi-Carter et al, 2002;Strand et al, 2005). Additionally, we previously discovered that skeletal muscle from R6/2 transgenic HD mice is hyperexcitable due to decreased currents through chloride (ClC-1) and inwardly rectifying potassium (Kir) channels, which correlated with aberrant mRNA processing and lower levels of mature full-length mRNAs for ClC-1 and Kir channels (Waters et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The depletion of the Na + (or the accumulation of K + ) could reduce the muscle membrane excitability sufficiently to explain the force loss during a higher frequency (Moritani et al, 1985). Frontiers in Physiology | www.frontiersin.org Due to different stimulation protocols and other environmental conditions, the comparison of the results presented here to other animal studies remains complicated (Guo et al, 2012;Kobayashi et al, 2012;Tsutaki et al, 2013;Hering et al, 2016;Li et al, 2016;Valenzuela et al, 2017). Nevertheless, similar results could be observed in the behavior of the muscle during stimulation with different frequencies, even if the environmental influences and the way of stimulation of the muscle (ex vivo, needle electrode) were different.…”
Section: Discussionmentioning
confidence: 84%
“…The question now arises why we could not find an increased shortening at higher frequencies, what the force frequency relationship (FFR) suggests. Studies found an increase in muscle tension (Guo et al, 2012) or strength production (Hering et al, 2016) due to an increase in the frequency in animal experiments. First of all, it has to be taken into account that our experiments are carried out ex vivo, using a needle electrode, which complicates the comparability to in vivo or in vitro studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation